A private model for determining the efficiency of target distribution - М.С. Піскунов; В.Є. Кудряшов; О.В. Філіппенков (Системи озброєння і військова техніка)
A specific model has been developed to assess the performance indicators of target designation when setting obstacles by the enemy and maneuvering various targets. On the basis of the adopted technical characteristics and parameters of stations and weapon systems, optimal target designation options were found. Favorable conditions for firing rockets have also been determined. The indicator of the increase in the average number of destroyed targets is calculated when moving from one type of target placement to another. The course of solving a specific model is presented. Analytical expressions for calculating target indicators of placement efficiency and graphic material are given.